Histological examination of various tissues in rats with hypothyroidism induced by propylthiouracil or thyroidectomy - Mogulkoç, R; Canpolat, L; Baltaci, AK; Yilmaz, B; Kelestimur, H (Lippincott Williams & Wilkins, 1999)
Despite the common use of propylthiouracil (PTU) to induce hypothyroidism, it causes degeneration of the thyroid gland, kidney and anterior pituitary tissue. The aim of our study was to determine changes in the liver, thyroid gland, kidney and anterior pituitary from male rats treated with PTU (10 mg/kg/day; for 2 weeks) and in thyroidectomy-induced hypothyroid male rats. Histological examination was performed by light microscopy. Total T3 and T4 levels were determined by radioimmunassay. In both PTU-treated and thyroidectomized groups, plasma T3 and T4 levels were significantly lower than those in the control group. No abnormal changes were observed in the liver tis sue of the hypothyroid rats. There were significant decreases in the epithelial magnitude of degenerated follicular cells in the thyroid tissues of the PTU-treated animals. Furthermore, these were seen in the lumen, which did not contain colloid. There was mononuclear cell infiltration and haemorrhage in the kidney cortex and medulla in both the thyroidectomized and PTU groups. The anterior pituitary in the thyroidectomized and PTU-treated rats showed a diffused hyperplasia. The tissue was locally haemorrhagic, and basophilic cells were frequently localized at the side of the haemorrhage. These findings show that both PTU and thyroidectomy-induced hypothyroidism causes changes in the histology of the kidney, thyroid gland and anterior pituitary. Med Sci Res 27:801-805 (C) 1999 Lippincott Williams & Wilkins.
Keywords: anterior pituitary; hypothyroidism; kidney; liver; propylthiouracil